Regulation of Integrin Subunit Alpha 2 by miR-135b-5p Modulates Chemoresistance in Gastric Cancer - Wang, Qi; Cao, Tianyu; Guo, Kai; Zhou, Yao; Liu, Hao; Pan, Yanan; Hou, Qiuqiu; Nie, Yongzhan; Fan, Daiming; Lu, Yuanyuan; Zhao, Xiaodi (Frontiers in Oncology, 2020)
Chemotherapy has substantially improved gastric cancer (GC) patient outcomes in the past decades. However, the development of chemotherapy resistance has become the major cause of treatment failure. Although numerous molecules have been implicated in GC chemoresistance, its pathological mechanisms are still unclear. Here, we found that integrin subunit alpha 2 (ITGA2) is upregulated in chemoresistant GC cells and that increased ITGA2 levels correlated with the poor prognosis of GC patients who received chemotherapy. ITGA2 overexpression led to elevated chemotherapy resistance and drug-induced apoptosis inhibition in GC cells. ITGA2 knockdown resulted in restored chemosensitivity and increased apoptosis in chemoresistant GC cells both in vitro and in vivo. NanoString analysis revealed a unique signature of deregulated pathway expression in GC cells after ITGA2 silencing. The MAPK/ERK pathway and epithelial-mesenchymal transition (EMT) were found to be downregulated after ITGA2 knockdown. miR-135b-5p was identified as a direct upstream regulator of ITGA2. miR-135b-5p overexpression reduced chemoresistance and induced apoptosis in GC cells and attenuated ITGA2-induced chemoresistance and antiapoptotic effects by inhibiting MAPK signaling and EMT. In conclusion, this study underscored the role and mechanism of ITGA2 in GC and suggested the novel miR-135b-5p/ITGA2 axis as an epigenetic cause of chemoresistance with diagnostic and therapeutic implications.